CHILDREN FRIENDLY SCHOOLING TO FULFILL THE RIGHT TO EDUCATION - Resti Nurhayati, Bernadeta (Jurnal Komunikasi Hukum, 2020)
Children are heir of a nation’s future. Therefore, they ought to be comprehensively prepared both physically and psychologically in order to reach desired adulthood. Parents, trustee, and teachers together play important roles in this regard. To reach impeccable adulthood, fulfilling certain education extenthas been serving obligatory purpose since long time ago. Generally, one child’s education and well-being have been parent’s responsibility. However, stateguarantees every child access to proper education fulfillment, as it is written on UUD 1945 article 28 C, which ensures citizen development via basic physical needs fulfillment, including getting education and benefit from science, art, and cultural advantages in order to improve quality life. Yet in the middle of the process, sometimes they face obstacles in form of physical and psychological harassment. It can be, they find it delivered through playing groups, teaching teams, or surrounding adults. The complication has to be ignorance to education in general and school reluctant specifically. If the effect carries over they would eventually loss the opportunity of getting education rights served right.This paper aims to study access to education in general, harassment in school environment, and children-friendly school as an effort to fulfill education rights.According to the study the author concludes that education rights serve as one of human rights. Consequently, government guarantee its access to ensure education rights served right, including carrying out feasible actions and countermeasure to prevent and resolve problems in the society. The author would like to suggest children-friendly schooling in every city or regency in Indonesia.Key words: children rights, education rights, children-friendly school